First live sighting of an Indo-Pacific humpback dolphin (Sousa chinensis) in the Yellow Sea, the northern-most record of the species range. (14th August 2022) - Lin, Wenzhi; Wu, Lan; Zeng, Qianhui; Leng, Xiaoyu; Mo, Yaqian; Serres, Agathe; Li, Songhai
Abstract: An opportunistic sighting of an Indo-Pacific humpback dolphin ( Sousa chinensis ) was reported in the nearshore waters off the east Liaodong Peninsula, China. This is the first at-sea sighting in this area, and the northern-most sighting record of this species with a distance >3000 km away from the nearest described conspecific population located in the mid-China. The present sighting occurred in close proximity to the location at which another Indo-Pacific humpback dolphin was found by-caught in 2003. The sighted individual could not be identified through the existing photo-identification catalogues of this species in China (>3500 individuals). Therefore, we suggest that a population of Indo-Pacific humpback dolphins that was never reported might exist in the north of the Yellow Sea.